2021
DOI: 10.3390/chemengineering5020027
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Attitudes towards Microalgae Production and Microalgae-Based Agricultural Products: The Cases of Almería (Spain) and Livorno (Italy)

Abstract: The production of microalgal biomass and products derived thereof for a wide variety of applications is a hot research topic, with the number of facilities being built and products and biologically active molecules launched into the market increasing every year. The aim of the current study was to identify the attitudes of citizens in Almería (Spain) and Livorno (Italy) towards the construction of a microalgae production plant and a biorefinery in their cities and also their opinions about the microalgae-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…These results are consistent with previous reports indicating a negative correlation between watercress seed germination and the concentration of Scenedesmus sp. extracts [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. In addition, a previous work revealed that bioactive molecules, such as abscisic acid (ABA), could produce shoot growth suppression (by themselves) and form an inhibitory complex along with other biomolecules, such as lunularic acids [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with previous reports indicating a negative correlation between watercress seed germination and the concentration of Scenedesmus sp. extracts [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. In addition, a previous work revealed that bioactive molecules, such as abscisic acid (ABA), could produce shoot growth suppression (by themselves) and form an inhibitory complex along with other biomolecules, such as lunularic acids [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Their compositions include various hormones such as auxins, gibberellins, and cytokinins, which, despite being present in small quantities, provide the algal extracts with marked effects that translate into various agronomic benefits [ 8 ]. Microalgae production and microalgae-derived products offer many advantages, such as reduced environmental impact and widespread consumer acceptance [ 9 , 10 ]. Moreover, these microorganisms can be produced on nonarable land and using different types of water and nutrient sources, including agricultural waste and urban wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…The color and typical “marine” taste of microalgae are not generally appreciated by many consumers. Several studies are finding strategies to mask the undesirable flavors either by incorporating microalgae in food formulations, by adding spices [ 149 ], or by modifying the aromatic profile through fermentation [ 150 ]. However, the sensory issue is far from being mitigated.…”
Section: Challenges and Future Prospectsmentioning
confidence: 99%
“…Recently, a survey about consumer attitude toward microalgae-based agricultural products highlighted that farmers in the region of Almeria (Spain) and Livorno (Italy) were not in favor of building microalgal production facilities in their properties; however, the use of microalgae-based agricultural products such as biostimulants, biofertilizers and aquafeed in both locations was acceptable, especially in Livorno (Italy). Authors also highlighted the influence of farmers knowledge about microalgal biotechnologies and their benefits, whereas acceptance was fairly more positive when farmers gained more information [ 126 ].…”
Section: Commercialized Microalgae- and Cyanobacteria-based Biostimul...mentioning
confidence: 99%